Analysis of The Influence of Green Brand Positioning and Green Brand Knowledge on Brand Evangelism - Damanik, Winner; Batu, Kardison Lumban (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
This study aims to analyze the effect of green brand positioning and green brand knowledge on brand evangelism through attitude toward green brand and green product purchase intention on consumers of DANONE AQUA products in Semarang City. This research uses the Theory of Planned Behavior (TPB) as the main theoretical basis that covers all research variables. The research method used is quantitative using SEM AMOS. The sample size was set at 125 respondents, following the recommendations for SEM analysis. The results of data analysis show that green brand positioning has a positive and significant effect on attitude toward green brand and green product purchase intention. Green brand knowledge has a positive and insignificant effect on attitude toward green brand, while on green product purchase intention it has a positive and significant effect. Attitude toward green brand has a positive and insignificant effect on green product purchase intention. Furthermore, green product purchase intention has a significant positive effect on brand evangelism. The conclusion of this study is that efforts to improve green brand positioning and green brand knowledge can affect attitude toward green brand. Green product purchase intention turns out to play an important role in motivating consumers to become brand evangelist and contribute to green brand positioning. These findings provide valuable insights for businesses in developing green branding strategies and understanding consumer behavior related to green products